Current Approaches to Support the Psychosocial Care of African American Adults with Diabetes: A Brief Review - Mitchell, Jamie Ann (2014)
African Americans are disproportionately affected by type 2 diabetes and experience significantly higher age-adjusted prevalence of the disease. Psychosocial support, material resources, and education can have a significant impact on successful diabetes management, particularly among populations with diabetes-related psychological distress such as African Americans. This brief review of the literature identifies and synthesizes current evidence on faith-based, community-based, empowerment-based, strength-based, and culturally competent strategies that may be particularly relevant for social work practitioners supporting African American adults at risk for or diagnosed with Type 2 diabetes. Discussion focuses on multiple influences on the self-determination of clients working to manage their condition